Effects of serial and concurrent training on receptive identification tasks: A Systematic replication. Issue 3 (8th June 2017) - Wunderlich, Kara L.; Vollmer, Timothy R.
Abstract : The current study compared the use of serial and concurrent methods to train multiple exemplars when teaching receptive language skills, providing a systematic replication of Wunderlich, Vollmer, Donaldson, and Phillips (2014). Five preschoolers diagnosed with developmental delays or autism spectrum disorders were taught to receptively identify letters or letter sounds. Subjects learned the target stimuli slightly faster in concurrent training and a high degree of generalization was obtained following both methods of training, indicating that both the serial and concurrent methods of training are efficient and effective instructional procedures.